A facile approach for large-scale recovery of phosphogypsum: An insight from its performance. (22nd November 2021) - Cao, Wenxiang; Yi, Wei; Li, Jing; Peng, Jiahui; Yin, Suhong
Highlights: Calcination pretreatment is effective and facile method for recovery of PG. The impurities accelerated the hydration process at high calcination temperatures. The properties of untreated PG calcined at 800 °C significantly improved. Abstract: The calcination treatment for recycling phosphogypsum (PG) is very promising, which can transform PG into a binder material and remove harmful impurities. To effectively recycle and reutilize PG, the influence of calcination temperatures on the properties of calcined and hydrated PG with and without pretreatment should be investigated. This paper systematically studied the effect of calcination temperature on the properties of water-washed and untreated plaster. The calcined untreated (UPG) and water-washed PG (WPG) were characterized by an X-ray fluorescence spectrometer (XRF), X-ray diffraction analyzer (XRD), and isothermal calorimetry, as well as by determining water requirement for normal consistency, setting time, whereas hydrated PG products were characterized by XRD, differential scanning calorimetry (DSC), thermogravimetry (TG), derivative thermogravimetry (DTG), and scanning electron microscope (SEM), as well as by measuring the mechanical properties. The results show that the chemical and mineralogical composition of calcined untreated PG (CUG) is similar to that of calcined water-washed PG (CWG) at the same calcination temperatures, and higher temperatures resulted in lower F content but no change in P2 O5 content. At low calcination temperatures (150 °C–400 °C), the cumulative heat of CUG was lower than that of CWG, and the hydration rate is similar; however, the cumulative heat and hydration rate of CUG at 700 °C or 800 °C were much higher than that of CWG, resulting in the significant reduction in setting time. Hydrated CUG (HUG) showed tiny crystals with lower interlocking at low calcination temperatures, but a more compact microstructure with defined crystals was observed in the HUG-800 due to the high formation of dihydrate gypsum; thus, HUG calcined at low temperature showed a lower strength but at 800 °C showed the maximum strength. This work indicates that calcination at 800 °C showed a potential application for the recovery and utilization of raw PG because of its excellent performance.